2008
DOI: 10.1111/j.1600-0854.2007.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

A CD63 Mutant Inhibits T‐cell Tropic Human Immunodeficiency Virus Type 1 Entry by Disrupting CXCR4 Trafficking to the Plasma Membrane

Abstract: We have discovered that an N-terminal deletion mutant of a membrane protein, CD63, (CD63DN) blocks entry of CXCR4-using, T-cell tropic human immunodeficiency virus type 1 (X4 HIV-1) by suppressing CXCR4 surface expression. This suppression was observed for CXCR4 but not for CD4, CCR5, CD25, CD71 or other tetraspanin proteins. The suppression of CXCR4 expression on the plasma membrane appeared to be caused by mislocalization of CXCR4 and exclusive transportation of CXCR4 toward intracellular organelles, mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
59
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 46 publications
5
59
1
1
Order By: Relevance
“…It is possible, however, that endogenous GBA1 exerts its anti-EV71 effects through other mechanisms for a slight downregulation of cell surface SCARB2 expression. Few intrinsic negative regulators of viral infection have been reported to act through the attenuation of receptor trafficking [25]. To the best of our knowledge, our finding is unique in this regard.…”
Section: Discussioncontrasting
confidence: 44%
“…It is possible, however, that endogenous GBA1 exerts its anti-EV71 effects through other mechanisms for a slight downregulation of cell surface SCARB2 expression. Few intrinsic negative regulators of viral infection have been reported to act through the attenuation of receptor trafficking [25]. To the best of our knowledge, our finding is unique in this regard.…”
Section: Discussioncontrasting
confidence: 44%
“…4B) explain why the repression of virus-cell fusion was not observed previously. Finally, we asked whether the fusion-preventive functions of tetraspanins in producer cells (described in this report) were independent of their entry-inhibiting activities in target cells (14,18,47,51). The data presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, tetraspanins on uninfected (target) cells inhibit HIV-1-induced cell-cell fusion (14). This fusion regulation is likely due to interactions of CD9 and CD81 with CD4 and coreceptors at the surface of target cells, though the tetraspanin CD63 has also been implicated in the trafficking of CXCR4 to the plasma membrane (51).…”
mentioning
confidence: 99%
“…Although we were not able to show clear results proving IL-21-induced CXCR4 downregulation in centrocytes in vivo, IL-21 has a potential to control CXCR4 downregulation not only on activated B cells but also on GC B cells. Second, we showed that CD63, which traffics CXCR4 to late endosome in CD4 T cells (17), downregulates CXCR4 expression on activated B cells. The amount of CD63 mRNA was inversely correlated with that of Bcl6 mRNA in GC B cells, and the amount of CD63 protein was strikingly augmented in activated Bcl6 2/2 B cells.…”
Section: Discussionmentioning
confidence: 78%
“…The various endocytosis-related molecules including GRK6, b-arrestin2 (Arrb2), and AIP4 are inducible in CD4 T cells for the clathrin-dependent internalization of CXCR4 (13)(14)(15)(16). Of the exocytosis-related molecules, CD63, a ubiquitously expressed tetraspanin, has been identified as a negative regulator of CXCR4 exocytosis in CD4 T cells (17,18). CD63 interacts with CXCR4 directly through the N-linked glycans portion of CD63.…”
mentioning
confidence: 99%